Identification and characterization of diverse OTU deubiquitinases in bacteria. (22nd June 2020) - Schubert, Alexander F; Nguyen, Justine V; Franklin, Tyler G; Geurink, Paul P; Roberts, Cameron G; Sanderson, Daniel J; Miller, Lauren N; Ovaa, Huib; Hofmann, Kay; Pruneda, Jonathan N; Komander, David
Abstract: Manipulation of host ubiquitin signaling is becoming an increasingly apparent evolutionary strategy among bacterial and viral pathogens. By removing host ubiquitin signals, for example, invading pathogens can inactivate immune response pathways and evade detection. The ovarian tumor (OTU) family of deubiquitinases regulates diverse ubiquitin signals in humans. Viral pathogens have also extensively co‐opted the OTU fold to subvert host signaling, but the extent to which bacteria utilize the OTU fold was unknown. We have predicted and validated a set of OTU deubiquitinases encoded by several classes of pathogenic bacteria. Biochemical assays highlight the ubiquitin and polyubiquitin linkage specificities of these bacterial deubiquitinases. By determining the ubiquitin‐bound structures of two examples, we demonstrate the novel strategies that have evolved to both thread an OTU fold and recognize a ubiquitin substrate. With these new examples, we perform the first cross‐kingdom structural analysis of the OTU fold that highlights commonalities among distantly related OTU deubiquitinases. Synopsis: OTU‐family deubiquitinases (DUBs) regulate human ubiquitin signaling and have been subverted by viruses, while their use by pathogenic bacteria remains less‐well characterized. Broader identification and characterization of bacterial OTU DUBs now allows for first cross‐kingdom comparison of this deubiquitination enzyme fold. Bioinformatic prediction identifies eukaryote‐like OTU deubiquitinase domains across a broad set of bacterial species. Eight predicted bacterial OTU DUBs were recombinantly expressed and biochemically validated. Enzymology and crystal structures reveal novel ubiquitin interaction modes. An alternate direction of sequence threading through the OTU fold exemplifies a tolerance to permutation. Cross‐kingdom structural analysis of the OTU deubiquitinase fold allows categorizing the variable structural motifs responsible for interactions with substrate ubiquitin. Abstract : Prediction and validation of pathogenic bacterial DUBs and insights into their structures and (poly)ubiquitin linkage specificities allows for first cross‐kingdom comparison of the OTU deubiquitination enzyme fold.